COCONUT SUGAR BUSINESS DEVELOPMENT IN SARI MANGGAR COCONUT SUGAR CRAFTERS THROUGH MOLD DESIGN AND MARKETING - Herlina Herlina; Ketut Indraningrat; Dewi Prihatini; Elok Sri Utami; Yuli Wibowo (UNEJ e-Proceeding, 2022)
The industry that has the potential to be developed and produce export-worthy products in Banyuwangi district is the coconut sugar processing industry. This industry is generally managed by craftsmen scattered in various remote rural areas. The partner of this activity is a group of coconut palm sugar craftsmen in the hamlet of Gumuk Agung, Gintangan village, Blimbingsari sub-district. Coconut sugar products produced by the Sari Manggar craftsman group are less able to develop as expected, the sugar produced is of low quality, the mold is not uniform and the marketing is local so that the welfare of the coconut farmers / craftsmen does not change much and their contribution to regional income is also low. The purpose of this activity is to improve the quality of coconut sugar through mold design and marketing of coconut sugar. Therefore, it is necessary to find a solution to engineer the mold design and improve promotion and marketing. The methods used in this activity are: 1) Observation; 2) Interview; 3)Training; 4) Sugar processing demonstration; and 5) Assistance in online promotion and marketing. The results of the activity show that the implementation of service can be carried out 100%, coconut sugar craftsmen Sari Manggar can produce coconut sugar in a cylindrical shape that weighs 100g/piece and is in a half ball shape, and coconut sugar craftsmen can do promotion and marketing online. Keywords: coconut sugar, coconut sugar craftsmen, print design, online marketing